Influences of Chemical Functionalities on Crystal Structures and Electrochemical Properties of Dihydro-benzoxazine Dimer Derivatives - Natapol Suetrong; Kantapat Chansaenpak; Sarawoot Impeng; Piyanut Pinyou; Vincent Blay; Rubén Blay-Roger; Sireerat Lisnund; Pongsakorn Kanjanaboos; Yuranan Hanlumyuang; Suttipong Wannapaiboon; Worawat Wattanathana (Crystals, 2021)
Dihydro-1,3,2H-benzoxazine dimer derivatives or dihydro-benzoxazine dimers are a class of compounds typically prepared by ring-opening reactions between dihydro-benzoxazines and phenols. Dihydro-benzoxazine dimers act as chelating agents for several transition and rare-earth cations. To better understand the chelating properties, it is necessary to examine their structural features and electrochemical characteristics thoroughly. However, the electrochemical properties of dihydro-benzoxazine dimers have not been tremendously examined. Herein, eight derivatives of dihydro-benzoxazine dimers possessing different substituents on the benzene ring and the tertiary-amine nitrogen were synthesized as model compounds to investigate their influences on crystal structures and electrochemical properties. The crystal structure of the dihydro-benzoxazine dimer, namely 2,2′-(cyclohexylazanediyl)bis(methylene)bis(4-methoxyphenol) (7), is identified for the first time and further used to compare with the crystal structures of other derivatives reported previously. For all the derivatives, intermolecular O–H⋅⋅⋅O hydrogen bonds are the significant interactions to hold the crystal packing of (7) and also the other derivatives. Hirshfeld surface analyses confirm the presence of intermolecular O–H⋅⋅⋅O hydrogen bonds. Redox behavior of the eight dihydro-benzoxazine dimers was studied by cyclic voltammetry. An oxidation peak observed at 0.25–0.47 V corresponds to the oxidation of the phenolic –OH group to the phenoxonium intermediate. The shift in the electrochemical peak positions is due to the different abilities of the substituents to stabilize the phenoxonium cation intermediate. The stabilizing power is ranged in the following order: methoxy > dimethyl > ethyl ≈ methyl, and N-cyclohexyl > N-methyl. Thus, the derivative (7), which contains both the methoxy and N-cyclohexyl groups, has the lowest oxidation potential. Our work elucidates the effect of the substituents on the crystal structures and electrochemical properties of the dihydro-benzoxazine dimers.